2008
DOI: 10.1038/onc.2008.402
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of neuroblastoma growth by dipeptidyl peptidase IV: relevance of chemokine regulation and caspase activation

Abstract: Imbalanced protease expression and activities may contribute to the development of cancers including neuroblastoma. Neuroblastoma is a fatal childhood cancer of the sympathetic nervous system that frequently overexpresses mitogenic peptides, chemokines and their receptors. Dipeptidyl peptidase IV (DPPIV), a cell surface serine protease, inactivates or degrades some of these bioactive peptides and chemokines, thereby regulating cell proliferation and survival. Our studies show that DPPIV is expressed in normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 62 publications
4
53
0
Order By: Relevance
“…Complementary DNA (cDNA) was synthesized from 5 µg of total RNA using 0.5 µg of Oligo(dT) 15 -primer (Roche Diagnostics) and SuperScript ® III Reverse Transcriptase (Invitrogen) as per the manufacturer's instructions. Quantitative measurements of DPs and PEP mRNA levels were determined by real-time qPCR using TaqMan™ probe technology and external PCR product standards of known copy number.…”
Section: Rna Isolation and Real-time Quantitative Pcr (Qpcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Complementary DNA (cDNA) was synthesized from 5 µg of total RNA using 0.5 µg of Oligo(dT) 15 -primer (Roche Diagnostics) and SuperScript ® III Reverse Transcriptase (Invitrogen) as per the manufacturer's instructions. Quantitative measurements of DPs and PEP mRNA levels were determined by real-time qPCR using TaqMan™ probe technology and external PCR product standards of known copy number.…”
Section: Rna Isolation and Real-time Quantitative Pcr (Qpcr)mentioning
confidence: 99%
“…Notably, the chemokine CXC12 [stromal derived factor 1 (SDF-1)], a known endogenous DP4 substrate (9) which is also cleaved by DP8 in vitro (7) and its receptor, CXCR4, form a CXC12/CXCR4 axis that appears to play an important role in tumor cell proliferation and metastases of numerous cancers including breast and epithelial ovarian cancer (10-12). DP4 proteolysis inactivates SDF-1α/β, disrupting the SDF-1/ CXCR4 interaction affecting downstream signaling and the likely SDF-1 mediated cell migration and metastasis (13)(14)(15) …”
Section: Introductionmentioning
confidence: 99%
“…In the Burkitt's B-cell lymphoma line DPP4 overexpression results in elevated p38 mitogen-activated protein kinases [MAPK; extracellular signal regulated kinase (ERK1/2)] phosphorylation (18). Using the nonselective DPP inhibitor Diprotin A, Arscott and colleagues showed that DPP4 enzyme activity downregulates fetal calf serum (FCS) stimulated Akt phosphorylation in the neuroblastoma cell line, SK-N-AS (2). However, an important remaining question is whether DPP4 could function as a cytoplasmic signaling enzyme in addition to its extracellular dipeptidyl peptidase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the kidney is where DPP-4 is expressed at the highest level per organ weight (13). Interestingly, DPP-4 has been associated with cell survival signaling and extracellular matrix remodelings (14)(15)(16).…”
mentioning
confidence: 99%